Identification of Genes Reveals the Mechanism of Cell Ferroptosis in Diabetic Nephropathy - Wang, Xian; Jiang, Ling; Liu, Xue-Qi; Huang, Yue-Bo; Zhu, Wei; Zeng, Han-Xu; Gao, Li; Ma, Li-Juan; Zhang, Meng-Ya; Zhu, Qi-Jin; Wu, Yong-Gui (Frontiers in Physiology, 2022)
Aims/introduction: Diabetic nephropathy (DN) is one of the main complications of diabetes. Genomics may reveal the essential pathogenesis of DN. We analyzed datasets to search for key genes to explore pathological mechanisms of DN. Materials and Methods: In this study, weighted gene co-expression network analysis (WGCNA) was used to divide the differential expression genes (DEGs) from GSE142025 into different modules, and enrichment pathway analysis was conducted for each module to find key genes related to cell death pathway. Then, verification was carried out through network and histopathology. Finally, the regulatory mechanisms of key gene expression, including transcription factors (TFs), miRNA and E3 ligases related to ubiquitination, were predicted through website prediction and then miRNA results were validated using GSE51674 dataset. Results：The results of WGCNA and enrichment pathway analysis indicated that ferroptosis had significantly occurred in advanced DN (AND) group. Analysis of DEGs indicated that the occurrence and development of ferroptosis are mainly through ALOX15-mediated lipid metabolism pathway, which was found in all intrinsic cells of the glomerulus detected by IHC and IF staining. Moreover, network predictions were used for searching ALOX15-related TFs and ubiquitination. Meanwhile, the network predictions combining with other dataset furtherly discovered miRNAs which regulated ALOX15 expression. This study showed that the levels of mmu-miR-142-3p increased in DN mice kidney tissues, compared with the NC group. Conclusion：Ferroptosis existed in glomerular intrinsic cells of ADN group and its potential key candidate gene was ALOX15 which may be regulated by miR-142 and miRNA-650, TFs (CREBBP, EP300, HDAC1, MTA1, SPI1, STAT6) and E3 ligases related to ubiquitination (PML, ZMIZ1, MARCHF1, MARCHF3, MARCHF8, MARCHF11).